The CLT Approach and Its Influence on Speaking Proficiency - Awololon, Yohanes Octovianus L.; Purwaningsih, Lilik (LPPM Universitas Dhyana Pura, 2025)
The objective of this study is to investigate the influence of the Communicative Language Teaching (CLT) approach on the speaking ability of first-grade students. A quantitative method was employed, specifically a quasi-experimental design. There were two classes selected: one as the experimental group (X) and the other as the control group (Y). The participants were the first-grade students of SMAN 2 Kupang in the 2024/2025 academic year. Class A and Class B were chosen as the samples using purposive sampling. A questionnaire was administered to assess the perceptions of the experimental group regarding the implementation of the CLT approach. In addition, tests were conducted to measure studentsâ€™ progress in speaking ability, and classroom observations were carried out to monitor student engagement during the application of the CLT approach. Based on the comparison between pre-test and post-test results, studentsâ€™ post-test scores were higher than their pre-test scores. The results of the hypothesis testing showed that the calculated t-value is 12.503, which exceeded the critical t-value of 1.701 (tâ‚ â‰¥ tâ‚œ). Therefore, the null hypothesis (Hâ‚€) is rejected and the alternative hypothesis (Hâ‚) is accepted. These findings indicated that the implementation of the CLT approach was effective in improving the speaking ability of first-grade students.